Avaliação energética e otimização da produção de briquetes a partir do resíduo da madeira da poda e da cama de ave - Marreiro, Hívila Maria Pontes (2022)
Biomass in its natural form has precarious characteristics such as low density, high moisture content and low energy density. However, through physical, thermochemical or biochemical conversion routes, it is possible to use it as an energy source. The present work made use of the physical conversion of densification of two residual biomasses, being them the wood of the urban pruning of the species Neem (Azadirachta indica) and the poultry litter. The process used was briquetting, which consists of the uniformization and agglomeration of biomass particles, transforming them into a solid fuel, whose characteristics must follow a quality standard determined by international standards. The main characteristics of briquettes are high density and compressive strength, low moisture content (MC), Higher Heating Value (HHV) and energy density. Such characteristics allow biofuel to be easily transported, handled and stored, in addition to ensuring more efficient and uniform combustion. Therefore, briquettes were produced following the experimental research methodology. First, a systematic literature review (RSL) was carried out to verify existing publications in the area. Through this review it was identified that 95% of the publications use granulometry as a process variable, 73% use compression pressure, 68% the initial moisture content and 59% use the compaction time. These results helped in the decision of the control and response variables to be evaluated in conducting the experiments according to the response surface methodology (RSM). The output variables were empirically modeled and statistically validated by ANOVA, R²adj, normality of residuals, influential observations and Lack-of-Fit. The control variables selected were the biomass compression load, compaction time, proportion of poultry litter and pruning wood to compose the briquettes and granulometry. The output variables were briquette density, moisture content MC and HHV. After obtaining the validated mathematical models, a multi-objective optimization was performed to simultaneously maximize the density and HHV and minimize the TU. For this, the Normalized Global Criterion Method (MCGN) was applied, using the Generalized Reduced Gradient (GRG). Experimentally, HHV of 24.18MJ/kg, density of 1252.02kg/m³ and MC of 9.05% were obtained. Such results prove the physical and energetic potential of pruning wood and poultry litter as biofuel.